Extranasal Rhinosporidiosis: A Case Report - Patil, D. R.; Thatte, M. R.; Thatte, R. L. (Indian Journal of Plastic Surgery, 1987)
Clinical findings, pharmacological control and the surgical treatment adopted in an unusual case of extranasal rhinosporidiosis without a nasal lesion is being presented.